Lipid nanoparticles based on natural matrices with activity against multidrug resistant bacterial species - da Silva, Elenice Francisco; Bastos, Luciana Machado; Fonseca, Belchiolina Beatriz; Ribas, Rosineide Marques; Sommerfeld, Simone; Pires, Henrique Machado; dos Santos, Fernanda Aparecida Longato; Ribeiro, Lígia Nunes de Morais (Frontiers in Cellular and Infection Microbiology, 2024)
Lately, the bacterial multidrug resistance has been a reason to public health concerning around world. The development of new pharmacology therapies against infections caused by multidrug-resistant bacteria is urgent. In this work, we developed 10 NLC formulations composed of essential oils (EO), vegetable butter and surfactant. The formulations were evaluated for long-term and thermal cycling stability studies in terms of (particle size, polydispersion index and Zeta potential). In vitro antimicrobial assays were performed using disk diffusion test and by the determination of the minimum inhibitory concentration (MIC) performed with fresh and a year-old NLC. The most promising system and its excipients were structurally characterized through experimental methodologies (FTIR-ATR, DSC and FE-SEM). Finally, this same formulation was studied through nanotoxicity assays on the chicken embryo model, analyzing different parameters, as viability and weight changes of embryos and annexes. All the developed formulations presented long-term physicochemical and thermal stability. The formulation based on cinnamon EO presented in vitro activity against strains of Acinetobacter baumannii, Klebsiella pneumoniae and Pseudomonas aeruginosa isolated from humans and in vivo biocompatibility. Considering these promising results, such system is able to be further tested on in vivo efficacy assays. NOTE: Means in the same column followed by distinct asterisks differ statistically from each other p < 0.05 (One way ANOVA followed by Tukey test); * Represents the highest values of means similar to each other; ** Represents the second highest values of similar means; *** Represents the third highest values of similar means.